Odpowiedź :
Odpowiedź:
[tex]a=8 \cdot 10^{15}[/tex]
[tex]\sqrt[3]{a}=\sqrt[3]{8 \cdot 10^{15}} =\sqrt[3]{8} \cdot \sqrt[3]{10^{15}} =2 \cdot (10^{\frac{1}{3}})^{15}=2 \cdot 10^5[/tex]
Pierwsze zdanie jest fałszywe.
[tex]\sqrt[3]{a^2} =\sqrt[3]{(8 \cdot 10^{15})^2}=\sqrt[3]{8^2} \cdot \sqrt[3]{(10^{15})^2}=\sqrt[3]{64} \cdot \sqrt[3]{10^{30}} =4 } \cdot 10^{10}[/tex]
Drugie zdanie jest prawdziwe.
Wzory z jakich skorzystaliśmy :
[tex]a^{\frac{m}{n}}=\sqrt[n]{a^m}[/tex]
[tex]\sqrt[n]{a \cdot b} =\sqrt[n]{a} \cdot \sqrt[n]{b}[/tex]
Odpowiedź:
1) [tex]\sqrt[3]{a} = \sqrt[3]{8*10^{15} } = \sqrt[3]{8} * \sqrt[3]{10^{15} } = 2 * 10^{5}[/tex] zatem FAŁSZ
2) [tex]\sqrt[3]{a^2} = \sqrt[3]{(8*10^{15})^2} = \sqrt[3]{64*10^{30}} = \sqrt[3]{64} * \sqrt[3]{10^{30} } = 4 * 10^{10}[/tex] zatem PRAWDA